Pepper Trade from Lampung to Banten and Its Influence on Social Titles in the 17th Century - Oktaviani, Cesaria Ria; Lestari, Della Dwi; Ismiani, Meza Meza; Anisa, Siti siti; Jaiz, Syifana Auliani; Khasanah, Uswatun (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This research discusses the Lampung Pepper Trade to Banten and its influence on social status in the 17th century. This research uses historical research methods, namely, heuristics, source criticism, interpretation and historiography. This research found that the people of Lampung obtained social status after selling Lada to the Banten sultanate based on certain heavy provisions. The awarding of the title occurred because of Lampung's close relationship with Banten, which was driven by the importance of the pepper trade at that time. As the main commodity, pepper connects Lampung with the international trade network through the port of Banten. The Sultanate of Banten built good relations with the people of Lampung to maintain a stable supply of pepper and meet the ever-increasing global demand. This trade point not only had an impact on the economy but also influenced the social structure in Lampung. The social title given reflected close economic interactions as well as changes in status. Lampung social community.